2014
DOI: 10.3904/kjim.2014.29.6.713
|View full text |Cite
|
Sign up to set email alerts
|

Recent advances in treatment of aplastic anemia

Abstract: Recent advances in the treatment of aplastic anemia (AA) made most of patients to expect to achieve a long-term survival. Allogeneic stem cell transplantation (SCT) from HLA-matched sibling donor (MSD-SCT) is a preferred first-line treatment option for younger patients with severe or very severe AA, whereas immunosuppressive treatment (IST) is an alternative option for others. Horse anti-thymocyte globuline (ATG) with cyclosporin A (CsA) had been a standard IST regimen with acceptable response rate. Recently, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
25
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 95 publications
0
25
0
1
Order By: Relevance
“…Both immunosuppressive therapy and allogeneic HSCT represent definite therapies for patients with SAA [11,12,20,21]. MSD-HSCT is the preferred first-line treatment option for younger (≤50 years) SAA patients [22]. GVHD and GR, both of which are critically influenced by the composition of the (27) .075 IFD 15 (26) 16 (29) .701 CMV viremia 14 (24) 12 (22) .770…”
Section: Discussionmentioning
confidence: 99%
“…Both immunosuppressive therapy and allogeneic HSCT represent definite therapies for patients with SAA [11,12,20,21]. MSD-HSCT is the preferred first-line treatment option for younger (≤50 years) SAA patients [22]. GVHD and GR, both of which are critically influenced by the composition of the (27) .075 IFD 15 (26) 16 (29) .701 CMV viremia 14 (24) 12 (22) .770…”
Section: Discussionmentioning
confidence: 99%
“…1 For younger (⩽40 years) patients with severe AA (SAA), if they have a suitable donors, allogeneic stem cell transplantation (SCT) from HLA-matched sibling donor (MSD-SCT) is the most preferred first-line treatment, [2][3][4] whereas its applications to older patients (440 years) is limited because of inferior outcomes or no advantage compared with the alternative treatment option of immunosuppressive therapy with antithymocyte globulin (ATG) and cyclosporin A. [5][6][7][8][9] Until recently, cyclophosphamide (Cy; 200 mg/kg) ± ATG had been the most widely used conditioning regimen for patients with SAA who received MSD-SCT.…”
Section: Introductionmentioning
confidence: 97%
“…In addition to first‐line standard treatment for AA, such as IST and HSCT, developing small novel molecules which could be used to correct the differentiation imbalance of AA BM‐MSCs or improve the AA BM microenvironment is of great value. Cheng et al reported that arsenic trioxide (ATO) exerts its clinical efficacy in treating AA patients by inhibiting adipogenic differentiation and facilitating osteogenic differentiation through increasing BMP4 expression, implicating its potential wide‐spread clinical application in AA therapy.…”
Section: Discussionmentioning
confidence: 99%